Relevant Problems of Implementing State Policy in the Field of Ensuring Information Security of Ukraine - Ye. V. Kobko; V. A. Kobko (Law and Safety)
The emphasis has been placed on the fact that the state is currently aware of the importance of information security within its territory and takes a number of important steps in this direction, such as the development of a new Information Security Strategy. However, such steps are difficult to consider objective, since they do not take into account a number of legal and organizational problems that need to be addressed promptly. Such problems include the following. First of all, the existence of an extensive regulatory and legal base in the information sphere in general and ensuring economic security, in particular. A large number of laws and by-laws different in their content and essence significantly complicates the development of comprehensive measures to ensure information security of Ukraine, and therefore needs to be improved. The latter can be implemented by codifying the said regulatory and legal base and by adopting the Code of Ukraine on Information and Information Relations, where a separate Section will be focused on information security issues. Secondly, the current conditions, where Ukraine finds itself, require the government to quickly adopt a new modern Information Security Strategy, which will include a number of measures aimed at improving such security level, since the latter is undoubtedly one of the important components of national security. Thirdly, the issue of ensuring certain aspects of information security is attributed to the tasks of various state authorities (Parliament, Government, executive authorities, law enforcement agencies, etc.). Moreover, such issues should be addressed at the local level by both legal entities and individuals, in the latter case we can talk about the personal information security of each person. This multiplicity of subjects of information security and the difference in their powers necessitates the creation of an appropriate coordinating agency with special powers in the mentioned area.